2022
DOI: 10.3390/microorganisms10061197
|View full text |Cite
|
Sign up to set email alerts
|

Role of Marine Bacterial Contaminants in Histamine Formation in Seafood Products: A Review

Abstract: Histamine is a toxic biogenic amine commonly found in seafood products or their derivatives. This metabolite is produced by histamine-producing bacteria (HPB) such as Proteus vulgaris, P. mirabilis, Enterobacter aerogenes, E. cloacae, Serratia fonticola, S. liquefaciens, Citrobacter freundii, C. braakii, Clostridium spp., Raoultella planticola, R. ornithinolytica, Vibrio alginolyticus, V. parahaemolyticus, V. olivaceus, Acinetobacter lowffi, Plesiomonas shigelloides, Pseudomonas putida, P. fluorescens, Aeromon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 101 publications
(164 reference statements)
0
11
0
1
Order By: Relevance
“…33 The toxic BA HIS is commonly found in seafood products or their derivatives and is produced by HIS-producing bacteria, such as Pseudomonas putida and P. fluorescens. 51 The initial levels of BAs in fresh fillets of seabass were found to be extremely low in this study. However, as the storage time increased, there was a gradual and evident increase in the levels of BAs observed in both water-treated and nisin-treated fillets.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…33 The toxic BA HIS is commonly found in seafood products or their derivatives and is produced by HIS-producing bacteria, such as Pseudomonas putida and P. fluorescens. 51 The initial levels of BAs in fresh fillets of seabass were found to be extremely low in this study. However, as the storage time increased, there was a gradual and evident increase in the levels of BAs observed in both water-treated and nisin-treated fillets.…”
Section: Discussionmentioning
confidence: 44%
“…Additionally, S. putrefaciens exhibited significantly higher PUT production abilities compared with other genera in grass carp ( Ctenopharyngodon idellus ) fillets during storage at 4 °C 33 . The toxic BA HIS is commonly found in seafood products or their derivatives and is produced by HIS‐producing bacteria, such as Pseudomonas putida and P. fluorescens 51 . The initial levels of BAs in fresh fillets of seabass were found to be extremely low in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Some Staphylococcus had certain pathogenicity and it showed an increased trend in the salting stage (Swolna & Wojtyczka, 2022). Previous studies had reported that Pseudomonas was the dominant amine‐producing bacterium and it was related to the metabolism of some carbohydrates and nitrogenous compounds (except lysine) which could affect the synthesis of flavour substances (Oktariani et al ., 2022). In the post‐fermentation stage, the abundance of these potentially harmful microorganisms ( Pseudomonas and Staphylococcus ) decreased and their abundance in the finished product (S14) were 5.28% and 6.93%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, Raoultella ornithinolytica has become increasingly important in human diseases ( 3 , 4 ), with infections being underreported because it is difficult to identify by routine biochemical and phenotypic methods ( 3 , 5 ). In addition, R. ornithinolytica causes histamine poisoning in fish (scombroid syndrome) and, after consumption, also in humans, due to its capacity to convert histidine to histamine ( 6 , 7 ).…”
Section: Announcementmentioning
confidence: 99%